2016
DOI: 10.1016/j.fertnstert.2016.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between paternal somatic health and assisted reproductive technology outcomes

Abstract: The current report identified a possible relationship between a man's health history and IVF outcomes. As these are potentially modifiable factors, further research should determine whether treatment for men's health conditions may improve or impair IVF outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The investigators suggested that the presence of erectile dysfunction in infertile men, particularly men with azoospermia, might prompt physicians to evaluate possible subclinical underlying morbidities. An early diagnosis of erectile dysfunction and the identification of its risk factors can provide useful information for eventually stratifying cardiovascular risk 26,27,121,139,140 . Whether or not erectile dysfunction in infertile men might be an earlier marker of cardiovascular diseases needs further investigation.…”
Section: Male Infertility and General Health A Proxy Of General Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators suggested that the presence of erectile dysfunction in infertile men, particularly men with azoospermia, might prompt physicians to evaluate possible subclinical underlying morbidities. An early diagnosis of erectile dysfunction and the identification of its risk factors can provide useful information for eventually stratifying cardiovascular risk 26,27,121,139,140 . Whether or not erectile dysfunction in infertile men might be an earlier marker of cardiovascular diseases needs further investigation.…”
Section: Male Infertility and General Health A Proxy Of General Healthmentioning
confidence: 99%
“…Decreased general health status is associated with impaired male sexual 22 and reproductive 23 health. The concept that male infertility might be an early marker of poor general health is emerging 15,[24][25][26][27] .…”
mentioning
confidence: 99%
“…Fourth, the association between the overall health status and treatment of men and ART outcome remains unclear. A recent study suggested that a man's health status may also be associated with ART success and the birth characteristics of the child (23). Although enhanced spermatogenesis per se was improved by comorbidity treatment, further research should determine whether the treatment of the health conditions of men might influence ART outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, paternal lifestyle and environmental effects could affect offspring via epigenetic changes in spermatozoa influencing offspring phenotype 3,4 . While most studies of paternal influences on offspring to date have explored unassisted conception, much less is known in regard to paternal factors and outcomes within assisted reproductive technologies (ART) though poor paternal health may negatively impact outcomes 5 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 While most studies of paternal influences on offspring to date have explored unassisted conception, much less is known in regard to paternal factors and outcomes within assisted reproductive technologies (ART) though poor paternal health may negatively impact outcomes. 5 Male factor infertility accounts for about 30%-50% of all evaluations of infertility with 7% of men worldwide eventually labeled infertile. 6 As such, a large portion of those couples undergoing ART will utilize semen that may have altered parameters.…”
Section: Introductionmentioning
confidence: 99%